Radionuclides Determination and Hazard Indices Assessment of NORM Contaminated Soil for Oil Fields in Southern Iraq - Ibrahim, Zaidoon H.; Al-Mashhadani, Asia H. (Iraqi Journal of Science, 2024)
Oil and gas extraction greatly impacts the environment due to the existence of natural radionuclides in crude oil. Uncontrolled dealing with the extraction can lead to radiological contamination. This research aims to determine the radioactivity concentration of naturally occurring radioactive materials (NORM) and risk assessment of contaminated soil in oil fields. Three oil fields in Al- Basra government southern of Iraq were investigated; 45 soil samples were collected from several locations, the first group of soil samples from Al Rumaila southern oil field, the second group was collected from Khudair Almay storage site, and the third group collected from a waste pit near an oil-well in Majnoon oil field. High purity germanium (HPGe) detector was used to determine the radioactivity concentrations of radionuclides of the series 238U and 232Th as well as 40K. The mean concentration of 226Ra, 228Ra, and 40K was found in the soil samples of the first group: 5.625×104±1.5%, 5.157×103±1.43%, and 1.744×103±5.7% Bq kg-1, respectively, 1.07×105±1.5%, 7.90×103±1.43% and 8.33×102 ±5.7% Bq kg-1, respectively for the second group and 4.85×102±5.7%, 5.5×101±9% and 1.65×103±15.9% Bq kg-1, respectively for the third group. The hazard indices, total radium equivalent, representative gamma level index, and annual effective dose equivalent were calculated to estimate the potential radiological health risk in these oil fields. The results fluctuate as acceptance in some samples of the third group and not acceptance in most of the first and the second group soil samples.         The statistical analyses of data show a high positive correlation coefficient (r= 0.996) with significant p-value (p≤0.05) and coefficient of determination (R2= 0.993) between 226Ra and 228Ra in the first and second groups soil samples, whereas there is no correlation in the third group.